2000
DOI: 10.1007/s002990050006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient wheat transformation procedure: transformed calli with long-term morphogenic potential for plant regeneration

Abstract: Langenberg, W.G.; Mitra, Amitava; and French, Roy C., "An efficient wheat transformation procedure: transformed calli with long-term morphogenic potential for plant regeneration" (2000). Abstract A method for producing large numbers of transgenic wheat plants has been developed. With this approach, an average of 9.7% of immature embryo explants were transformed and generated multiple selffertile, independently transformed plants. No untransformed plants, or escapes, were regenerated. This transformation proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 36 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…Substantial data have been generated recently on wheat transformation protocols (Liu et al 2000;Sorikin et al 2000;Vasil et al 1992;Witrzens et al 1998;Zhang et al 2000), and gene expression (Muller et al 1996;Rooke et al 2000;Takumi et al 1997), thereby providing an essential background for the development of a system for the mass production of bread wheat transgenic plants. For durum wheat, however, the rate of success has been substantially lower, with only a few investigations to be found in the published literature (Bommineni et al 1997;He et al 1999;Martin et al 1999;Tosi et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Substantial data have been generated recently on wheat transformation protocols (Liu et al 2000;Sorikin et al 2000;Vasil et al 1992;Witrzens et al 1998;Zhang et al 2000), and gene expression (Muller et al 1996;Rooke et al 2000;Takumi et al 1997), thereby providing an essential background for the development of a system for the mass production of bread wheat transgenic plants. For durum wheat, however, the rate of success has been substantially lower, with only a few investigations to be found in the published literature (Bommineni et al 1997;He et al 1999;Martin et al 1999;Tosi et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…The majority of wheat transformation investigations that have been reported (Vasil et al 1992(Vasil et al , 1993Weeks et al 1993;Nehra et al 1994;Becker et al 1994;Zhou et al 1995;Altpeter et al 1996; Barro et al 1998;Zhang et al 2000) utilized microparticle bombardment technology (Sanford 1988). Cheng et al (1997) first reported the success of Agrobacterium-mediated transformation in wheat using immature embryos and embryogenic calli to produce fertile transgenic plants.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of investigations were carried out on the optimization of conditions for the improved Agrobacterium-mediated genetic transformation in this major crop (Weir et al 2001;Wu et al 2003;Patnaik et al 2006;Yao et al 2007) but the transformation efficiency remained low (mostly around 1%) even the model cultivars were used (Weeks et al 1993;Nehra et al 1994;Cheng et al 1997). Increased frequencies were achieved by introduction of high responsive wheat genotypes such as model cultivar Bobwhite (9.3%) (Zhang et al 2000) and generally transformation protocols were further optimized using model cultivars with a relatively high embryogenic capacity (Janakiraman et al 2002). However, established protocols have a restricted application on elite and other wheat cultivars due to a wide range of variability in regeneration and transformation responses between varieties.…”
Section: Discussionmentioning
confidence: 99%